2022
DOI: 10.1177/20406223221081616
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain omega-3 polyunsaturated fatty acids and the risk of heart failure

Abstract: Aims: Adequate intake of long-chain (LC) omega-3 polyunsaturated fatty acids ( n-3 PUFAs) is considered important for cardiovascular health. However, the effects of LC n-3 PUFAs on the risk of heart failure (HF) remain unclear. This systematic review and meta-analysis aimed to determine the role of LC n-3 PUFAs in the incidence of HF. Materials and Methods: Electronic databases were searched for studies up to 31 July 2021. Studies were included for the meta-analysis if they reported the adjusted associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…In 2017, Marques et al demonstrated the importance of consuming a high-fiber diet and supplementing with SCFAs to lower blood pressure, minimize cardiac remodeling, and inhibit cardiac hypertrophy and fibrosis through the modification of gut microbial modulation ( 26 ). Evidence from a meta-analysis by Zheng et al suggested that high long-chain omega-3 polyunsaturated fatty acids (LC n-3 PUFAs), obtained in the diet from seafood or in the form of supplements, may have preventive effects on heart failure ( 59 ). Therefore, the modulation of dietary composition and intestinal metabolites are expected to be new therapeutic targets of heart failure treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Marques et al demonstrated the importance of consuming a high-fiber diet and supplementing with SCFAs to lower blood pressure, minimize cardiac remodeling, and inhibit cardiac hypertrophy and fibrosis through the modification of gut microbial modulation ( 26 ). Evidence from a meta-analysis by Zheng et al suggested that high long-chain omega-3 polyunsaturated fatty acids (LC n-3 PUFAs), obtained in the diet from seafood or in the form of supplements, may have preventive effects on heart failure ( 59 ). Therefore, the modulation of dietary composition and intestinal metabolites are expected to be new therapeutic targets of heart failure treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the risk of bias using the Newcastle-Ottawa quality assessment scale for cohort studies and case-control studies ( 29 ). Cohort studies and case-control studies were classified as having low (≥7 stars), moderate (5–6 stars), and high risk of bias (≤4 stars) with an overall quality score of 9 stars ( 30 , 31 ). For cross-sectional studies, we assigned each item of the AHRQ checklist a score of 1 (answered “yes”) or 0 (answered “no” or “unclear”), and summarized scores across items to generate an overall quality score that ranged from 0 to 11.…”
Section: Methodsmentioning
confidence: 99%
“…Given the increasing prevalence and disease burden of HF along with the lack of approved pharmacological treatment, it is important to scour for modifiable risk factors and to develop preventive strategies. Previous studies have found significant relationships between dietary nutrients and HF ( 30 , 31 ). Our findings support a potentially adverse association between total, cereal dietary fiber and HF prevalence.…”
Section: Discussionmentioning
confidence: 90%